The evidence of Industrial Revolution 4.0 through the Adoption of Financial Technology (FINTECH) during COVID-19 pandemic among Malaysians - Alwi, Shaliza; Alpandi, Rabiatul Munirah; Yusof, Siti Hawa; Mohd Salleh, Masrina Nadia; Mohd Aslam, Siti Nor Aini; Roslan, Teh Raihana Nazirah; Ismail, Muhd Zulkifli; Tan, Say Peng (Kalahari Journals, 2022)
This study aims to further analyze the factors that contribute to the adoption of Financial Technology (FINTECH) among Malaysians during the COVID-19 pandemic. Financial institutions all over the world have been grappling with the consequences of the COVID-19 pandemic and striving to understand the immediate challenges to society, economies, and the long-term implications on the interconnected financial system during this time of crisis. As a result, this study will provide light on society's desire to adopt FINTECH in the face of the epidemic. A total of 402 surveys were distributed and gathered from FINTECH users between the ages of 18 and 60. SPSS was then used to examine the data. Consumers' intentions to use e-wallets during the COVID-19 pandemic are heavily influenced by performance expectations, effort expectations, social influence, and government support, as per the research findings. During the COVID-19 epidemic in Malaysia, researchers discovered that trust variants had no impact on customers' willingness to use e-wallets.